The Analysis of Workload and Work Environment on Nurse Performance with Job Stress as Mediation Variable - Yosiana Yosiana; Adya Hermawati; Muchlis H Mas’ud (Publisher of Widyagama University of Malang (UWG Press), 2020)
Nurses have a vital position in providing health services in the community in district areas. Their work situation needs to be considered in order to provide optimal service. This study aims to analyze the effect of workload and work environment on nurse performance and study work stress as a mediating variable on nurse performance. This research was carried out by using the survey approach to nurses working in Puskesmas in Tumpang district working area. Path analysis was applied to obtain the relationship between the variables studied. The results show that if high works are handled by a small number of human resources, it will only result in high workloads and then increase work stress. A conducive work environment not only helps nurses to control stress but also allows them to improve their performance.JEL Classification: I18, J24, M54